Address to the Economic and Social Council of the United Nations, December 20, 1966 - Woods, George D. (World Bank, Washington, DC, 2019)
George D. Woods, President of the World Bank Group, spoke about the Bank and IDA helping to put down the foundations of economic growth in the form of transportation and electric power projects, and going deeper into the development of human resources. He discussed the progress made by World Bank Group in the field of agriculture and education. He mentioned the drafting of a scheme for multilateral investment insurance. He highlighted aid coordination to accelerate development in developing countries. He concluded that the industrialized countries should make a joint and thorough examination of what they are trying to achieve in their relationships with the developing world.